The Impact of Teacher's Indirect Written Corrective Feedback on Eleventh Graders' Ability in Writing Explanation Texts - Septia Tri Gunawan; Ratna Sari Dewi; Zaharil An'asy (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis study is intended to acquire empirical evidence regarding the impact of the teacher's Indirect Written Corrective Feedback on students' writing ability of explanation texts. Fifty six students enrolling at a high school in Jakarta were selected as the sample. They were separately distributed in the experimental class and the control class that respectively contained 28 students. Purposive sampling was utilized to recognize who the research subjects were and what level of their competence was for inclusion in this study. A quasi-experimental design, which is a subpart of a quantitative method, was employed. The data were assembled by running a writing test in the pre-test and post-test sections, whose results were followed by normality and homogeneity tests. The findings showed that the experimental class’ post-test outcome was 64.71, while the control class’ post-test was 58.25. Since the t-value surpasses the t-table (2.502>1.675), it indicates that the teacher's Indirect Written Corrective Feedback has a significant effect on improving students' writing explanation texts.ABSTRAKStudi ini bertujuan untuk memperoleh bukti riil terkait pengaruh dari umpan balik tertulis tidak langsung oleh guru terhadap kemampuan siswa dalam menulis teks eksplanasi. 56 siswa yang bersekolah di sebuah sekolah menengah atas terpilih sebagai sampel. Siswa tersebut terbagi dalam kelas eksperimen dan kelas kontrol, yang masing-masing kelas berisikan 28 orang. Oleh karenanya, purposive sampling diterapkan karena peneliti sudah mengetahui siapa saja subjek penelitian dan kompetensi apa saja yang dimiliki. Desain kuasi-eksperimen yang merupakan sub-bagian dari metode kuantitatif digunakan oleh peneliti. Data diperoleh dengan mengadakan ujian tes tulis yang terdapat pada pra-tes dan pasca-tes yang diikuti dengna uji normalitas dan uji homogenitas. Hasil temuan menunjukkan bahwa rata-rata hasil pasca-tes yang diraih oleh siswa di kelas eksperimen sebesar 64.71, sedangkan 58.25 adalah hasil dari siswa kelas kontrol. Karena nilai t hitung melampaui nilai t tabel (2.502>1.675), maka hal tersebut menandakan umpan balik tertulis tidak langsung oleh guru memiliki dampak yang signifikan dalam meningkatkan kemampuan menulis siswa menulis teks eksplanasi.